Brachypterous ground beetles of the Trichotichnus subgenus Bottchrus Jedlička (Coleoptera, Carabidae) from the Himalaya, with description of fifteen new species - Kataev, Boris M.; Schmidt, Joachim (Zootaxa, 2017)
The paper deals with the taxonomy of brachypterous species of the subgenus Bottchrus Jedlička, 1935 of the genus Trichotichnus Morawitz, 1863 occurring in the Himalayan region. The following new species are described: T. (B.) baglungensis sp. n. from the Baglung Lekh mountain range, Baglung District, western Central Nepal; T. (B.) parvulus sp. n. from Mt. Panchhase and the Krapa Danda mountain range, Kaski District, western Central Nepal; T. (B.) bubsaensis sp. n. from the eastern slope of the middle Dudh Koshi Valley near Bubsa, Solu Khumbu District, eastern Central Nepal; T. (B.) schawalleri sp. n. from the western slope of the Arun Valley, Bhojpur District, East Nepal; T. (B.) obliquebasalis sp. n. from the Khimti Khola Valley near Shivalaya, Dolakha District, eastern Central Nepal; T. (B.) panchhaseensis sp. n. from Mt. Panchhase, Kaski District, western Central Nepal; T. (B.) siklesensis sp. n. from the Sikles mountain range on the southern slope of Annapurna Peak II, western Central Nepal; T. (B.) pusillus sp. n. from the south-western slopes of Manaslu Himal (Bara Pokhari Lekh and Dudh Pokhari Lekh mountain ranges), and from the south-eastern slope of Annapurna Himal (Telbrung Danda mountain range), Lamjung District, western Central Nepal; T. (B.) ganeshensis sp. n. from the south-western slope of Ganesh Himal, Nuwakot District, Central Nepal; T. (B.) minutus sp. n. from the mountains surrounding the Kathmandu Valley (Shivapuri Lekh, Mt. Phulchoki), Central Nepal; T. (B.) gupchiensis sp. n. from the Gupchi Danda mountain range on the south-eastern slope of Manaslu Himal, Gorkha District, western Central Nepal; T. (B.) brancuccii sp. n. from the southern slope of the Helambu mountain range, Sindhupalchok District, Central Nepal; T. (B.) manasluensis sp. n. from the Bara Pokhari Lekh mountain range on the south-western slope of Manaslu Himal, Lamjung District, western Central Nepal; T. (B.) sikkimensis sp. n. from Pelling near Geyzing, West Sikkim, India; T. (B.) martensi sp. n. from the western slopes of the Singalila mountain range, Taplejung District, East Nepal. The following four species are redescribed: brachypterous T. (B.) holzschuhi Kirschenhofer, 1992; T. (B.) cyanescens Ito, 1998; T. (B.) hingstoni Andrewes, 1930; and dimorphic T. (B.) birmanicus Bates, 1892; and new data on their distribution are provided. The lectotype is designated for T. hingstoni Andrewes, 1930. The following two new synonyms are proposed: Trichotichnus birmanicus Bates, 1892 = T. (Bellogenus) probsti Kirschenhofer, 1992, syn. n., and T. hingstoni Andrewes, 1930 = T. (Pseudotrichotichnus) curvatus Ito, 1996, syn. n. The brachypterous and dimorphic species of Bottchrus known from the Himalaya are divided into eight informal groups based mostly on the degree of reduction of hindwings and the configuration of the median lobe of the aedeagus, and their relationships are briefly discussed. The distributional data of all these species are mapped.